European Small Business Finance Outlook: June 2018 - Helmut Kraemer-Eis; Antonia Botsari; Salome Gvetadze; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2018)
This European Small Business Finance Outlook (ESBFO) provides an overview of the main markets relevant to EIF (equity, guarantees, securitisation, microfinance). It is an update of the December 2017 ESBFO edition. We start by discussing the general market environment, then look at the main aspects of equity finance and guarantees/SME Securitisation (SMESec). Finally, before we conclude, we briefly highlight some important aspects of microfinance and Fintech in Europe.
Keywords: 330